The prevalence of thrombophilia in patients with symptomatic peripheral vascular disease. - Vig, S; Chitolie, A; Bevan, D; Dormandy, J; Thompson, M; Halliday, A (Wiley, 2006)
Background The aim of this prospective study was to establish the prevalence of thrombophilia and hyperhomocysteinaemia using a comprehensive screen in patients with peripheral vascular disease. Methods A total of 150 patients with peripheral vascular disease (with an ankle brachial pressure index of less than 0·8) underwent thrombophilia screening (protein C and protein S, antithrombin, lupus anticoagulant, activated protein C resistance and factor V Leiden and prothrombin mutations). Fasting homocysteine assays were also performed. Results A thrombophilia defect was found in 41 patients (27·3 per cent). The commonest was protein S deficiency, found in 17 patients (11·3 per cent). Others included factor V Leiden mutation, found in 10 (6·7 per cent) and protein C deficiency, found in six (4·0 per cent). Lupus anticoagulant and prothrombin mutation were both found in six (4·0 per cent). One patient had an antithrombin deficiency. Only the presence of critical ischaemia was associated with a positive thrombophilia screen on single variable analysis (P=0·03). Hyperhomocysteinaemia was present in over a third of the study group (37·3 per cent): 45 defined as moderate and 11 as intermediate. Conclusion A quarter of patients with peripheral vascular disease had evidence of thrombophilia, and a third had hyperhomocysteinaemia.